Satellite tracking improves conservation outcomes for nesting hawksbill turtles in Solomon Islands. (September 2021) - Hamilton, Richard J.; Desbiens, Amelia; Pita, John; Brown, Christopher J.; Vuto, Simon; Atu, Willie; James, Robyn; Waldie, Peter; Limpus, Col
Abstract: The remote tracking of endangered animals is often justified by the application of movement data to conservation problems, but examples of where scientific findings have rapidly informed conservation actions are relatively rare. In this study we satellite tracked 30 adult female hawksbill turtles ( Eretmochelys imbricata ) that were captured after nesting in the Arnavon Community Marine Park (ACMP), Solomon Islands. Ten hawksbill turtles were tagged in April 2016, ten in May 2017 and ten in November 2018. Our primary aim was to determine if the ACMP boundaries that were demarcated in 1995 were large enough to protect female hawksbill turtles throughout their entire nesting season. Our home range analysis revealed that collectively, tracked hawksbill turtles spent 98.5% of their inter-nesting season within the ACMP, confirming that the original park boundaries were adequate. Our first year's results were shared with community and government stakeholders and assisted in getting the ACMP declared as the Solomon Islands first national park in May 2017. Our fine scale analysis of inter-nesting habitats also highlighted that most hawksbill turtle nests were being laid on an island in the ACMP that did not have a permanent ranger presence and was experiencing persistent poaching. Based on this finding an additional ranger station was established on this uninhabited island and staffed with community rangers in 2017. Our study demonstrates how involving community, government and NGO stakeholders in applied research can lead to results being rapidly utilised to inform policy and conservation practice as soon as they become available.